2008
DOI: 10.2139/ssrn.868708
|View full text |Cite
|
Sign up to set email alerts
|

Insider Trading Legislation and Acquisition Announcements: Do Laws Matter?

Abstract: In this paper we investigate how the enactment and enforcement of insider trading restrictions affect the way in which information about acquisitions is released before the actual acquisition announcement. We analyze a sample with almost 19,000 acquisition announcements from 48 countries. We find that insider trading legislation strongly affects the information revealed to the market in the runup phase before the announcement whereas the impact of subsequent enforcement actions by regulators is much weaker and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The influence of other public information is also stressed by Gu and Kurov (2018), who find that public forecasts made by analysts with a superior historical forecasting ability explain a significant part of the pre-announcement price run-ups before Author Manuscript rumours and/or public information sources might be synonymous with insider trading as traders obtaining illegal information are incentivized to spread rumours in the financial press to increase the value of their position. Maug et al (2008) analysed price run-ups in 48 countries and 18,752 takeover announcements. They found that passing insider trading legislation affects the pre-bid stock price run-ups: these run-ups explain less of the total price movements once insider trading legislation is in place.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The influence of other public information is also stressed by Gu and Kurov (2018), who find that public forecasts made by analysts with a superior historical forecasting ability explain a significant part of the pre-announcement price run-ups before Author Manuscript rumours and/or public information sources might be synonymous with insider trading as traders obtaining illegal information are incentivized to spread rumours in the financial press to increase the value of their position. Maug et al (2008) analysed price run-ups in 48 countries and 18,752 takeover announcements. They found that passing insider trading legislation affects the pre-bid stock price run-ups: these run-ups explain less of the total price movements once insider trading legislation is in place.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Although the finance and securities law literatures have long argued whether insider trading should be regulated at all (e.g., Manne (1966), Kyle (1985), Cornell and Sirri (1992), and Cao, Field, and Hanka (2004)), most regulatory agencies have prohibited insider trading on private, price-relevant information to encourage outside investors to participate in financial markets, lessen the risk of adverse selection, and improve liquidity and market efficiency (see Chung and Charoenwong (1998), Fishman and Hagerty (1992), Seyhun (1986), Fishe and Robe (2004), Ausubel (1990), DeMarzo, Fishman, and Hagerty (1998), and Fernandes and Ferreira (2009)). The enforcement of such provisions predicts decreasing cost of capital and increasing participation by investors and analysts (e.g., Bhattacharya and Daouk (2002), Christensen, Hail, and Leuz (2016), Maug, Van Halteren, and Ackerman (2008), and Bushman, Piotroski, and Smith (2005)).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Although the finance and securities law literatures have long argued whether insider trading should be regulated at all (e.g., Manne (1966), Kyle (1985), Cornell and Sirri (1992), and Cao, Field, and Hanka (2004)), most regulatory agencies have prohibited insider trading on private, price-relevant information to encourage outside investors to participate in financial markets, lessen the risk of adverse selection, and improve liquidity and market efficiency (see Chung and Charoenwong (1998), Fishman and Hagerty (1992), Seyhun (1986), Fishe and Robe (2004), Ausubel (1990), DeMarzo, Fishman, andHagerty (1998), and Fernandes and Ferreira (2009)). The enforcement of such provisions predicts decreasing cost of capital and increasing participation by investors and analysts (e.g., Bhattacharya and Daouk (2002), Christensen, Hail, and Leuz (2016), Maug, Van Halteren, andAckerman (2008), andBushman, Piotroski, andSmith (2005)).…”
Section: Background and Literature Reviewmentioning
confidence: 99%